Pengaruh PENGARUH KEBIASAAN MEMBACA TERHADAP KEMAMPUAN BERBICARA BAHASA INGGRIS SMA Negeri 99 Jakarta - Rofiq Noorman Haryadi (Jurnal Manajemen Bisnis dan Keuangan, 2020)
The purpose of its study was to determine reading habits toward English speaking skills. The research method used was a survey to determine the effect of reading habits on English speaking skills. Regarding data of reading habits were obtained through a questionnaire compiled by researcher. Meanwhile, regarding data of English speaking skill was secondary, it obtained the results of the students' scores from the English teacher. The results of the analysis show that 1) there is an effect of a positive influence between reading habits on the speaking skills of students at SMA Negeri 99 Jakarta. This is indicated by the correlation coefficient rcount of 0.739 which is more than the r table, namely rxy = 0.739> t 0.5 (1:30) = 0.349. The t value is then consulted on the t value table, and the results show at the 5% level t table 0.5 (1:28) = 2.048. These results indicate that the t test is more than t table. 2) The effect of two variables is expressed by the linear regression line equation with Ŷ = a + b X, namely Ŷ = 18.90 + 0.92 X. This equation shows that every one unit increase in the reading habit variable (X) scores on speaking skill (Y) is 18.90 in the constant 0.92. 3) The effort to find out whether or not the reading habit variable has an effect on the speaking skill variable can be shown by using one predictor regression analysis which results in a value of 2.23. 4) The value of the frequency was consulted with the Fisher (F) table on the value generated by the dkerror of 12 and dktc of 16, and the results showed 2.60. This means that the hypothesis, there is a positive influence between reading habits on the speaking skill of students at SMA Negeri 99 Jakarta has been proven. Thus, the analysis in this thesis is significant.